Teachers leadership in basic vocational training for mediation between school and employment of the students with intellectual functional diversity - María Isabel Negri Cortés; Juan José Leiva Olivencia (Universidad de La Rioja, 2019)
The Basic vocational training programs are a platform to the training and social and labor access of youngs with intellectual functional diversity, where the teachers have an essential role. The objective of our paper was to describe and analyze the leadership of the teacher when they act like mediators between scholar and labor contexts. We had an incidental sample made of 38 teachers of secondary education school of Málaga. The data were collected by an adhoc questionnaire that was valued for an expert group, and also by five depth interview to the participants of one of these schools. We applied the qualitative analysis to the interviews and the descriptive statistical analysis to the questionnaire data. The results point that is necessary the teachers work through shared leadership for teach habilities and skill that help to get a job to the students with intellectual functional diversity, being mediators between the training and social contexts. Like conclusion, is necessary to improve the initial training of the teachers and get better the curricular flexibilization and organization of the school.